2019
DOI: 10.3390/su11071874
|View full text |Cite
|
Sign up to set email alerts
|

How Consistent Contributors Inspire Individuals to Cooperate: The Role of Moral Elevation and Social Value Orientation

Abstract: Achieving cooperation to address social dilemmas has long been a global problem. This study examined, using an environment-focused step-level public-goods-dilemma game, the effect a consistent contributor (CC) has on group cooperation, as well as the mediating role moral elevation and the moderating role social value orientation (SVO) play in this process. A total of 196 students were recruited and classified as “pro-selfs” or “pro-socials” based on their SVOs; individuals with the same SVO characterization we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 102 publications
(161 reference statements)
1
17
0
Order By: Relevance
“…First, we did not want the other two confederates to contribute so little that they became free riders, overshadowing the effect of the CC. Furthermore, previous similar studies discovered that people's expectations of others' cooperation rates in the first round were around 70%, as were their actual cooperation rates (Zhang et al, 2019). In line with this, the current study found an average cooperation rate of 69% in the first round.…”
Section: Limitations and Future Studysupporting
confidence: 88%
See 3 more Smart Citations
“…First, we did not want the other two confederates to contribute so little that they became free riders, overshadowing the effect of the CC. Furthermore, previous similar studies discovered that people's expectations of others' cooperation rates in the first round were around 70%, as were their actual cooperation rates (Zhang et al, 2019). In line with this, the current study found an average cooperation rate of 69% in the first round.…”
Section: Limitations and Future Studysupporting
confidence: 88%
“…Consequently, not contributing to the public account (i.e., selfish behavior) is typically considered a rational strategy in such a dilemma, while contributing to the public account (i.e., cooperative behavior) is thought highly by people. The existence of the CC effect has been confirmed in many variants of public goods games, such as all-or-none, continuous, and step-level public goods games (Weber and Murnighan, 2008;Gill et al, 2013;Zhang et al, 2019). Several divergent accounts for explaining the CC effect have been proposed.…”
Section: Effectmentioning
confidence: 98%
See 2 more Smart Citations
“…To clarify these controversial results, we tested the influence of SVO coherent in the context of prisoner’s dilemma. Based on the findings of Zhang et al ( 2019 ), which suggest that four-pro-social-member groups are more cooperative than four-pro-self groups in the 15-rounds public-goods dilemma, we proposed the first hypothesis: Hypothesis 1: Dyadic SVO composition significantly influences dyad-level cooperation. Specifically, similar-pro-social dyads are most likely to achieve mutual cooperation, less so in different-SVO dyads, and least so in similar-pro-self dyads.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%